2021
DOI: 10.3390/ijerph18063107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Manure and Digestate Liquid Fractions Using Membranes: Opportunities and Challenges

Abstract: Manure and digestate liquid fractions are nutrient-rich effluents that can be fractionated and concentrated using membranes. However, these membranes tend to foul due to organic matter, solids, colloids, and inorganic compounds including calcium, ammonium, sodium, sulfur, potassium, phosphorus, and magnesium contained in the feed. This review paper is intended as a theoretical and practical tool for the decision-making process during design of membrane-based systems aiming at processing manure liquid fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 170 publications
(216 reference statements)
0
20
0
Order By: Relevance
“…Different membrane filtration processes, including micro-, ultra-, and nanofiltration, reverse osmosis, forward osmosis, membrane distillation and electrodialysis, have been developed or tested to treat the wet phase of separated digestate (Camilleri-Rumbau et al, 2021). Membranes are often based of polymeric compounds or aluminum or titan oxides.…”
Section: Membrane Filtration Technologiesmentioning
confidence: 99%
“…Different membrane filtration processes, including micro-, ultra-, and nanofiltration, reverse osmosis, forward osmosis, membrane distillation and electrodialysis, have been developed or tested to treat the wet phase of separated digestate (Camilleri-Rumbau et al, 2021). Membranes are often based of polymeric compounds or aluminum or titan oxides.…”
Section: Membrane Filtration Technologiesmentioning
confidence: 99%
“…However, without adequate treatment, the high concentrations of nutrients and organic compounds in liquid manure can have a negative effect on soil and water ecosystems [2][3][4]. Liquid manure also needs to be carefully managed to avoid odorous gas emissions and nutrient runoff into water sources [5]. As a consequence, the characteristics of liquid fertilizer are monitored to ensure that the quality is up to the required standards for application to farmland [6].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid swine manure (LSM) and anaerobic digestate (AD) are commonly used on farmland as organic fertilizers due to their high nutrient loads [5,11,12]. LSM contains all 13 essential nutrients [13], including 50-70% N, 90% K, and 35% P for plant consumption [14,15], while the high N, P, and K content in liquid or semiliquid AD increases its demand as a fertilizer [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This treatment provides heat for the pig houses where the pig manure can be continuously collected all year. The AD product, digestate, has been used widely as soil fertiliser because of its low cost compared with other approaches such as liquid-solid separation, pyrolysis of the solid fraction, and wastewater treatment for the liquid fraction (Camilleri-Rumbau et al, 2021; Zhang et al, 2021). Research has shown the fate of ARGs after AD treatment was dependent on AD starting modes, and most of the genes were carried by Firmicutes (Zhi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%